Verhinderung der vertikalen HIV1-Transmission: Ein Beispiel gelungener Präventivmedizin - Buchholz, Bernd; Hien, Steffen; Baumann, Ulrich (Monatsschrift Kinderheilkunde, 2012)
Background: Without any medical intervention to prevent mother-to-child transmission (MTCT) of HIV1 (human immunodeficiency virus), up to 40% of the HIV1-exposed newborns will become infected with HIV1. The combination of antiretroviral therapy of pregnant women, caesarean section scheduled before onset of labour, antiretroviral postexposure prophylaxis in the newborn and refraining from breastfeeding in those cases where HIV1 infection was known during pregnancy has since 1994 reduced the rate of vertical transmission of HIV1 to 1-2%. If HIV1 viral load is under the limit of detection prior to birth, even a vaginal delivery is meanwhile possible. Current state: Unfortunately in Germany more than 1% of children of HIV1-positive pregnant women are HIV1-infected. The main reasons in Germany are the lack of HIV1 testing of pregnant women (at present only 50-70%) and that recommendations for prophylaxis of MTCT of HIV1 were not followed. Conclusion: Only by periodically addressing these gaps of medical treatment in scientific articles and in lectures the acceptance for HIV1 testing (after counselling and agreement) in pregnancy can be raised and the recommendation-based treatment of the HIV1-positive pregnant woman and her offspring can be improved.